Development of digital comics SIPROMAN to improve students' critical thinking and creative thinking skills - Shania Putri Apriani; S. Supriyatin; R. Rusdi (University of Muhammadiyah Malang, 2025)
This study investigates the effectiveness of siproman digital comics as a learning medium to enhance critical and creative thinking skills in biology, specifically on the human reproductive system. Recognizing the importance of these skills in the 21st century and their current low levels among students, this research employed Educational Design Research (EDR) adapted from the Hannafin & Peck model. Data collection involved questionnaires, student needs analysis, and teacher interviews. Siproman comics were created using Autodesk-SketchBook and underwent feasibility testing by media and material experts, achieving average scores of 85% and 87%, indicating high feasibility. Product trials were conducted with teachers, small (12 students) and large (35 students) groups. A control group pre-test-post-test design, using instruments measuring eight critical thinking and six creative thinking skills, assessed effectiveness. Mancova testing revealed a significant difference (p<0.001) between groups across all criteria (Pillai's Trace, Wilks' Lambda, Hotelling's Trace, and Roy's Largest Root). These findings demonstrate that siproman digital comics are effective in improving students' critical and creative thinking skills.